Bolstering the Spatial Rotation Ability to Understand the Topics of Point and Line in Descriptive Geometry - Parra Lara, Hernando; Ospina Parra, Carlos Alberto (Ingeniería, 2024)
Objective: The main objective is to determine how the spatial rotation ability (HER) is enhanced in first-year engineering students of Universidad Tecnológica de Pereira (UTP). Methodology: A qualitative study is proposed which is aimed at understanding the role of students' prior ideas in the development of the HER. Initially, a test (PSVT: R) is administered to a group of students as a pre-test. Four of these students are selected using a Student's t-test. Then, an instrument that measures the notions regarding the concepts of point and line that students have developed since childhood is applied. Results: After conducting the post-test, progress in the students' HER is evident. This difference was statistically significant (p<0.05). The tests of the four selected students were analyzed using the Atlas ti software. Conclusions: The development of the HER was evidenced in the results of the normalized PSVT: R post-test, implying the evolution of students' (previous, vague, and imprecise) ideas regarding 3D notions of point and line.